Manejo integrado del perforador del fruto Cerconota anonella Sepp,1830 en el cultivo de guanábana Annona muricata y su impacto en el rendimiento - Reina Mosquera, Jennifer Elena (2022)
Soursop is a non-traditional fruit in Ecuador, it is also known by its scientific name of Annona muricata. They are bushes that produce soft fruits with their green skin with pimples and their pulp is sweet, juicy and fibrous, it normally grows in moderate climates, but over time it has been adapted to different climates, the suitable soil for soursop is those with a loamy or loamy-clay texture At the national level, the Annona muricata has a low demand due to the fact that in Ecuador the nutritional level and the benefits of this fruit are unknown, which despite not being produced as much, is exported to other countries. Soursop farmers have had to deal with pest insects, since these, if not detected in time, cause damage to the tree and in some cases, can kill it or lower its production. Soursop is affected by Cerconota anonella defoliators that cause considerable losses in the yield and quality of the fruit. These pest insects generally feed on the flowers, but if they are not detected in time, they attack the fruit, causing serious damage. That is why we have to control the defoliated in time, the best control methods are: cultural control, which consists of using plastic bags to bag the fruit, although in some cases it can rot the fruit; while in biological control some parasitoids and natural predators of Cerconota anonella have been found, which attack and eliminate them, although they are difficult to find and chemical control is the most used despite the fact that they are harmful to human health and contaminate the environment. environment, the most used insecticides are: Trichlorfon, Permethrin and Imidacloprid